A Analysis of Information System Audit Using Control Objectives for Information and Related Technology 5 Framework on Permata Hebat Application (Universitas Negeri Semarang, 2023)
Permata Hebat application is an application created as a service to develop micro businesses among housewifes in Semarang City. However, to fulfill this expectation, of course, the application needs good IT management or governance, so that the application can be optimally utilized by its users. However, since its operation on March 23, 2021, it is not yet known how the quality or level of management capability or IT governance services run by the organization. Information system audit itself is an activity to evaluate and ensure that the system has met the standards. Meanwhile, one of the frameworks that can be used to conduct an audit is COBIT 5. COBIT 5 is a good practice whose processes have been adapted to current standards. As for the process control used is the Deliver, Services, and Support (DSS) domain. The results of the calculation show that for domains DSS01, DSS03, and DSS06 each received a maturity level value of 0.60, 0.52, and 0.61 or at level 1 performed. Meanwhile, domains DSS02, DSS04, and DSS05 each received maturity level values of 0.45, 0.35, and 0.42 or are still at level 0 incomplete. Therefore, there is still a need for a lot of improvement or improvement in each process. The goal is that the system can run in accordance with organizational expectations.